Combination therapy with afatinib and bevacizumab in an EGFR-mutated non-small cell lung cancer patient with acquired ERBB2 amplification: A case report. Issue 8 (26th February 2021) - Chen, Sixian; Xiang, Tianmin; Lu, Wei; Hong, Shuiqiang; Li, Yuanyuan; Lu, Yuan; Zhang, Qiongyue; Chen, Yongfeng; Zhou, Suli; Wang, Gehui; Zhang, Zhenzhen; Cai, Yongguang
Abstract: Introduction: Acquired resistance to reversible EGFR tyrosine kinase inhibitors remains a significant obstacle, and acquired ERBB2 amplification is the most common "bypass" mechanism. For patients with sensitizing EGFR mutation who experience resistance via ERBB2 amplification, no targeted drug has been demonstrated to be effective. Patient concerns: A 56-year-old female nonsmoker suffered from left leg paralysis and low back pain. Imaging examination revealed a mass in the anterior segment of the right upper lobe lung and possible multiple metastases in the right hilar, mediastinal lymph nodes, bone metastases, and soft tissue invasion. Diagnosis: Transbronchial lung biopsy revealed a moderately differentiated adenocarcinoma (cT4N2M1c, stage IV). An EGFR exon 19 deletion was identified using amplification refractory mutation system. Interventions: After the patient was treated with gefitinib initiation (250 mg/d) for 15 months, the tumor progressed with ERBB2 amplification revealed by next-generation sequencing test. Then, the patient was started on afatinib (40 mg/d) plus bevacizumab (7.5 mg/kg every 3 weeks). Outcomes: The combination therapy of afatinib and bevacizumab in this patient was effective with some slight side effects. Computed tomography scans showed the tumor shrinkage and the pleural effusion disappeared in the right lung. The overall survival was 23.5 months. Conclusion: To date, there is no targeted therapy approved and demonstrated to be effective for non-small cell lung cancer patients with EGFR sensitizing mutations, and ERBB2 amplification. The effectiveness of combination therapy with afatinib and bevacizumab may provide a new therapeutic option for these patients.